Resolutions of IAE (First International Congress of Egyptology, 1979)
Purpose To evaluate plasma and aqueous humor angiotensin-converting enzyme (ACE) and transforming growth factor-β1 (TGF-β1) levels in patients with proliferative vitreoretinopathy (PVR) secondary to rhegmatogenous retinal detachment (RRD). Methods Eighty-eight patients were divided into three groups: RRD without PVR (non-PVR, n = 36), RRD with PVR (PVR, n = 32), and controls (n = 20). Plasma and aqueous ACE and TGF-β1 levels were quantified using ELISA. Group comparisons, regression, and receiving operating characteristics analyses were performed to determine associations with PVR. Results Age and sex did not differ among groups ( P > 0.05). Median aqueous ACE levels were significantly higher in PVR and non-PVR eyes than in controls (both P < 0.001), although the PVR-non-PVR difference was nonsignificant ( P = 0.411). Aqueous TGF-β1 levels were markedly elevated in the PVR group versus both others ( P < 0.001). Plasma ACE and TGF-β1 did not differ among groups ( P > 0.05). Aqueous TGF-β1 demonstrated strong discriminative performance for PVR within this cohort (area under the curve = 0.92; cutoff 132.0 ng/L; sensitivity 93.8%; specificity 72.2%). Multivariate analysis identified aqueous TGF-β1 (OR = 1.047, P = 0.002) and symptom duration >30 days (OR = 77.6, P = 0.014) as independent predictors. Aqueous ACE and TGF-β1 were positively correlated, although this association did not reach statistical significance (ρ = 0.230, P = 0.059). Conclusion Aqueous ACE and TGF-β1 levels were elevated in eyes with RRD. TGF-β1 was significantly associated with PVR, whereas ACE elevation appeared to reflect intraocular changes related to RRD rather than a PVR-specific process.